A review on vaccine pharmacovigilance during covid-19 - Navya, Jyothi K; Jaka, Archana; Velpula Padma sujaya, Velpula Padma sujaya; Rupavath, Pallavi Nayak; Vaddadi, Randeep Raj C (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2021)
Pharmacovigilance is important for collecting, detecting, monitoring adverse events which is the main objective. The adverse events reported should be assessed in order to know the casual relationship and avoid unnecessary effects on the recipient. Many people are vaccinating in a short period, so it is becoming much burden to the pharmacovigilance centers. The international society of pharmacovigilance (ISOP), the French national agency for medicines and health products safety (ANSM), and many others were in continuous collaboration and taking many initiatives to identify the safety and efficacy of vaccines and to provide answers to the raised questions respectively. Through pharmacovigilance, signals were detected, and many adverse events were identified. Pharmacovigilance of BioNTech/Pfizer-m-RNA, Moderna-mRNA vaccine, Covishield, Johnson and Johnson, Vaxzevria, Sputnik V, Convidecia are addressed. With BioNTech/Pfizer-m-RNA 12,249 ADRs, with Moderna-mRNA vaccine 577 ADRs, with Covishield 447 ADRs, with Johnson and Johnson 653 ADRs, with Vaxzevria 743 ADRs were reported. These vaccines resulted in immune thrombocytopenic purpura, cerebrovascular events, thrombosis, thrombocytopenia, facial paralysis, deaths, and many other reactions which may be fatal. But the events reported were less compared to the safety of the patients. All these events were maintained by the Uppsala monitoring center.